Health State Utility Values Associated with Cochlear Implants in Adults: A Systematic Review and Network Meta-Analysis. Issue 2 (28th October 2022) - Dixon, Peter R.; Shapiro, Justin; Tomlinson, George; Cottrell, Justin; Lui, Justin T.; Falk, Lindsey; Chen, Joseph M.
Abstract : Objectives: The cost-effectiveness of bilateral cochlear implants in adults remains uncertain despite established clinical benefits. In cost-effectiveness studies, benefit is often measured by change in health state utility value (HSUV), a single number summary of health-related quality of life anchored at 0 (state of being dead) and 1 (perfect health). Small differences in bilateral cochlear implant HSUV change conclusions of published models, and invalid estimates can therefore mislead policy and funding decisions. As such, we aimed to review and synthesize published HSUV estimates associated with cochlear implants. Design: We included observational or experimental studies reporting HSUV for adult patients (age ≥18 years) with at least moderate-profound sensorineural hearing loss in both ears who received unilateral or bilateral cochlear implants. We searched MEDLINE, EMBASE, PsycINFO, and Cochrane Library databases up to May 1, 2021. Study and participant characteristics and HSUV outcomes were extracted. Narrative synthesis is reported for all studies. A Bayesian network meta-analysis was conducted to generate pooled estimates for the mean difference in HSUV for three comparisons: (1) unilateral cochlear implant versus preimplant, (2) bilateral cochlear implants versus preimplant, (3) bilateral versus unilateral cochlear implants. Our principal measure was pooled mean difference in HSUV. Results: Thirty-six studies reporting unique patient cohorts were identified. Health Utilities Index, 3 (HUI-3) was the most common HSUV elicitation method. HSUV from 19 preimplant mean estimates (1402 patients), 19 unilateral cochlear implant mean estimates (1701 patients), and 5 bilateral cochlear implants mean estimates (83 patients) were pooled to estimate mean differences in HUI-3 HSUV by network meta-analysis. Compared with preimplant, a unilateral cochlear implant was associated with a mean change in HSUV of +0.17 (95% credible interval [CrI] +0.12 to +0.23) and bilateral cochlear implants were associated with a mean change of +0.25 (95% CrI +0.12 to +0.37). No significant difference in HSUV was detected for bilateral compared with unilateral cochlear implants (+0.08 [95% CrI −0.06 to +0.21]). Overall study quality was moderate. Conclusions: The findings of this review and network meta-analysis comprise the best-available resource for parameterization of cost-utility models of cochlear implantation in adults and highlight the need to critically evaluate the validity of available HSUV instruments for bilateral cochlear implant populations. Protocol registration: PROSPERO (CRD42018091838)